Calculus of directional coderivatives and normal cones in Asplund spaces - Long, Pujun; Wang, Bingwu; Yang, Xinmin (Positivity : an international journal devoted to the theory and applications of positivity in analysis, 2017)
We study the directional Mordukhovich normal cones to nonsmooth sets, coderivatives of set-valued mappings in Asplund spaces and establish extensive calculus results on these constructions under various operations of sets and mappings. We also develop calculus of the directional sequential normal compactness both in general Banach spaces and in Asplund spaces.